Analysis of the Distribution Pattern of Genetic Biomarkers of Safety of Etiotropic Drugs for the Treatment of COVID-19 in Representatives of Ethnic Groups of the Volga Region and the Far East - S. N. Tuchkova; Sh. P. Abdullaev; N. P. Denisenko; A. V. Kryukov; I. I. Temirbulatov; S. S. Suleymanov; E. Y. Kitaeva; V. V. Shprakh; E. E. Sidukova; I. V. Sychev; K. B. Mirzaev; D. A. Sychev (Антибиотики и Химиотерапия)
The effectiveness and safety of favipiravir may be determined by polymorphisms of genes encoding enzymes involved in the biotransformation of the drug — AOX1 and CYP1A2. The aim of the study was to analyze the distribution frequency of allelic variants of genes encoding enzymes involved in the biotransformation of favipiravir AOX1 (rs55754655 and rs10931910) and CYP1A2*F1 (rs762551) among ethnic groups of the Volga region and the Far East. Material and methods. The study involved 497 volunteers from five ethnic groups: Russians, Mari, Mordvins, Nanai, and Buryats. The definition of belonging to an ethnic group was determined by double self-identification. Biomarker carriage was determined by the RT-PCR method. Results. Statistically significant differences between ethnic groups were observed in relation to the studied single nucleotide polymorphisms. The frequency of occurrence of the mutant allele C rs10931910 AOX1 among the Nanai differs from all ethnic groups except the Buryats, and the minor allele C rs55754655 AOX1 was significantly different among the Mari. A difference was found in the distribution of the A allele of rs762551 CYP1A2*F1 between the Buryat and Russian groups. Distribution patterns corresponded to frequencies in the larger populations from which the studied subpopulations originated. The frequencies of occurrence of the C allele of rs55754655 AOX1 were 10% in Russians, 5% in Mari, 3% in Buryats, 7.5% in Mordvins, 3.5% in Nanai. Allele C rs10931910 AOX1 was detected in 48%, 42%, 86%, 36%, and 77.5%, respectively, polymorphism of the CYP1A2*F1 gene rs762551 (mutant allele — A) — 65%, 55%, 68%, 70%, and 74%, respectively. Conclusion. There is heterogeneity in the distribution of polymorphisms of genes and enzymes that metabolize drugs, including favipiravir, which may be important when personalizing therapy for patients representing certain ethnic groups of the Russian Federation.